Multipole Mixing Ratios of Gamma Rays From Fe(n,nÎ³) Fe 56 56 26 26 ï‚¢ Reaction Using Constant Statistical Tensor Method (CST). - Saied, B. M.; Yohana, H. M.; Younis, T. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The ï¤- Multiple mixing ratios of ï§-transitions from levels of 56Fe populated in 56 56 ( , ) Fe n n Fe ï§ ï‚¢ reactions are calculated by using const. S.T.M.  This method has been used in other works [3,7] but with pure transition or with  transitions that can be considered as pure transitionsØŒ in our work we used   This method for mixed ï§ - transitions in addition to pure ï§ - transitions. The experimental angular distribution coefficients a2 was used from previous works [1] in order to calculet ï¤- values. It is clear from the results that the ï¤- values are in good agreement or consistent, within associated errors, with those reported previously [1]. The discrepancies that occur are due to inaccuracies existing in the experimental data of the previous works. The present work results confirm the validities of C.S.T.M.  in calculating the ï¤-mixing ratios and their capabilities in predicting any inaccuracy in the experimental data and C.T.T.M. for mixed transition which are better than C.T.T.M. for pure transitions because it depends only on the experimental results while the 2nd method depends on pure and that which can be considered to be pure transitions.